Once upon two cities a parallel between New York City and Bucharest by 1900 - Neţ, Mariana 1956- (Common Ground Publishing, 2016)
"This book is an excursion into the past. It deals with two cities: New York and Bucharest in the era between 1865 and 1914. The two cities are representative of the two countries they belong to, but they are also important in themselves, qua cities. This is the era when both cities were being built and began to assert their identities, when they were becoming aware of their assets and starting to talk about them"...Preface
Includes bibliographical references (pages 259-273) and index
Keywords: Sozialgeschichte 1865-1914; City and town life -- New York (State) -- New York -- History; City and town life -- Romania -- Bucharest -- History; Stadtleben; New York (N.Y.) -- Description and travel; Bucharest (Romania) -- Description and travel; New York (N.Y.) -- Social life and customs -- 19th century; New York (N.Y.) -- Social life and customs -- 20th century; Bucharest (Romania) -- Social life and customs -- 19th century; Bucharest (Romania) -- Social life and customs -- 20th century; Bukarest; New York, NY